Revealing the local fatigue behavior of bimodal copper laminates by micropillar fatigue tests - Krauß, Sebastian; Schieß, Thomas; Göken, Mathias; Merle, Benoit (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
Cyclic micropillar compression is a powerful technique for characterizing the local fatigue properties of microstructurally complex materials. Here, it was applied to a bimodal copper sample made of alternating ultrafine and coarse grained layers. Micropillars were fabricated from both domains, as well as from the interface between them. The three different areas were investigated from the quasi-static to the high cycle fatigue range (up to 1 million cycles). In line with expectations, the CG micropillars exhibit the smallest fatigue strength and the UFG specimens the highest one. More surprisingly, the micropillars containing a bimodal UFG/CG interface exhibit a slightly shorter fatigue lifetime than plain UFG specimens. The likely reason is their more complex stress state, which alternates between tension and compression and results in the formation of surface extrusions, which lead to eventual failure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Bimodal microstructure; Copper; High cycle fatigue; Micropillar compression; Nanoindentation